Professional Learning Communities and Institutional Culture Change in Higher Education: Facilitators to Learning Ecological Validation to Support Historically Marginalized Students - Adrianna Kezar; Ronald E. Hallett; Zoë B. Corwin; Liane I. Hypolite; Mariama N. Nagbe (Journal of Postsecondary Student Success)
In this article, we explore how three campuses implemented professional learning communities (PLCs) in order to create institutional change in support of culture change (toward ecological validation) to support at-promise student success. The study explores the process of learning within the PLCs, examines facilitators of learning ecological validation, and discusses the viability of PLCs as a vehicle to undergo such learning in support of institutional culture change. The findings identify six conditions that support learning within PLCs in higher education settings aimed at culture change and these are distinctive from findings in the K-12 literature on PLCs.